When Evidence Doesn’t Work (Editorial) - Lindsay Glynn (University of Alberta, 2007)
I was listening intently to a discussion on the radio recently between Newfoundland and Labrador’s Minister of Education and aprofessor from Memorial University’s Math Department. They were debating the efficacy of the math curriculum in the province’s school system. As a parent of a grade 3 student, I have my own thoughts on how the curriculum is affecting kids’ math skills (and their anxiety levels, but let’s not go there). The professor echoed the concern that parents, teachers and students have been expressing: quite simply, it’s not working. Far too many children are failing math and are struggling with the both the content and pace of the required modules. Why am I telling you this? One particular comment made by the Minister of Education struck me. She said that there was evidence to suggest that this curriculum should work. While I’m always delighted to see the evidence based practice model being used, particularly for the betterment of my kids’education, it is dismaying to see that it is not always applied well. In this particular case, evidence was collected from somewhere and a decision was made to implement a new math curriculum based on the gathered evidence. Assuming that this truly was good evidence upon which to base such a decision, then I would have to concede that the appropriate steps were taken up until that point. Unfortunately, it appears that the entire process stopped there. As we know, one of the most important components of a thorough ebp‐based implementation is an internal evaluation. What might work somewhere else is not guaranteed to work in another environment, and it is essential to determine why an implementation or intervention worked or didn’t work. It would seem, in this case, that formal evaluations of the effectiveness of the new math curriculum have not been performed and therefore, the powers that be rely solely on the fact that it worked somewhere else. This is not evidence based practice at its finest.So, what happens when evidence doesn’t work? We try to figure out why ...